2013
DOI: 10.1097/aln.0b013e31829ab018
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane in Contrast to Propofol Promotes Fluid Extravasation during Cardiopulmonary Bypass in Pigs

Abstract: During CPB, isoflurane, in contrast to propofol, significantly contributes to a general increase in fluid shifts from the intravascular to the interstitial space with edema formation and a possible negative impact on postoperative organ function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…; Brekke et al. ) by increasing vascular permeability in the lungs and other organs (Kandatsu et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…; Brekke et al. ) by increasing vascular permeability in the lungs and other organs (Kandatsu et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in cardiac rate or rhythm were not observed during isoflurane anesthesia. [39][40][41][42][43] Studies [44][45][46] have revealed that isotonic crystalloids are rapidly eliminated from the intravascular (central) fluid compartment during isoflurane anesthesia and that IV fluid redistribution to peripheral tissues (interstitial tissue) is independent of the volume of fluid infused and markedly influenced by hypotension. [18][19][20]33 In contemporary human medicine, the type (crystalloid or colloid), volume (liberal or restricted), and rate of fluid administration during the perioperative period have become controversial issues.…”
Section: Discussionmentioning
confidence: 99%
“…Non‐pulsatile pump flow was set to 100 ml/kg/min. To obtain constant and controlled total body perfusion, a 9 V DC battery was set onto the right ventricle to induce ventricular fibrillation as previously described . CPB pump head pressures were in the range of 200–250 mmHg.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we demonstrated increased fluid extravasation during CPB when isoflurane was chosen as anesthetic agent, compared to propofol . Based on the reports of more favorable effects of sevoflurane on CFC and glycocalyx, and the negative effects of isoflurane with respect to microvascular permeability as reported, we hypothesized a difference with respect to fluid extravasation and edema generation when sevoflurane was compared to isoflurane during CPB.…”
mentioning
confidence: 93%